THE EFFECT OF LEXICAL COLLOCATION UPON STUDENTS’ READING COMPREHENSION ACHIEVEMENT AT SMAN 4 SINGARAJA IN THE ACADEMIC YEARS 2013/2014 - Venikagitayani, N. P. V.; Ratminingsih, M.; Suputra, P. E. D. (Universitas Pendidikan Ganesha, 2019)
AbstractThis experimental research aimed at investigating the effect of Lexical Collocation on students’ reading comprehension achievement. To conduct the research, 72 students were selected as the samples. They were the tenth grade students of science major at SMAN 4 Singaraja. The group of students were given the lottery, and the result showed that the X MIPA 2 was experimental group and X MIPA 3 was the control group. The design used in this research was Post Test Only Control Group Design. The experimental group was given collocation as treatment and the control group was taught by using a conventional teaching method. At the end, both experimental and control groups were given the post test. The post test was a reading comprehension test, consisting of 20 multiple choices. The data obtained by the post test were analysed by using Descriptive and Inferential Statistic Analyses. This study used alternative hyphothesis. The result of t test in which tobserved was higher than tcritical value 2.03 was 5.14. Based on the result, the null hyphothesis was rejected and the alternative hyphothesis was accepted. The rejected null hyphothesis means that there is significant difference on reading comprehension between the students who were taught by using collocation and who were not.Key words:Lexical Collocation, Conventional teaching reading, Reading comprehension.